Rural Areas of Surkhandarya Region and Their Specificity - Maxanov Sharofiddin Komil Ogli (Zien Journals, 2022)
The article describes the geography of rural areas, demography of rural areas, their specificity, as well as rural areas of Surkhandarya region and their specificity.
Keywords: Geography of rural areas; rural; demography of rural areas; rural population